Legal Analysis Of Administrative Court Decision No. 16/G/2024/PTUN.JKT In A Civil Service Dispute - Cucu Robiatul Adawiah; Intan Nuraeni; Zorya Kanoubie Attar Bakhri; Bakhri3Muhammad Rafa Nur Hidayat; Taufiq Alamsyah (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study examines Administrative Court Decision Number 16/G/2024/PTUN.JKT concerning a civil service dispute through a normative juridical approach that combines statutory, case based, and conceptual analyses. The research evaluates the legal validity of the contested administrative decision by examining the applicable regulatory framework, the judicial reasoning adopted by the court, and the relevance of the General Principles of Good Governance in administrative adjudication. The findings indicate that the court applied a comprehensive assessment of administrative legality by scrutinizing the conformity of governmental action with statutory requirements, procedural obligations, and governance standards recognized in Indonesian administrative law. The decision affirms the importance of legal certainty, accountability, transparency, and fairness as essential benchmarks for evaluating administrative conduct. The analysis further demonstrates that judicial review serves as an effective mechanism for protecting civil servants from arbitrary personnel actions while reinforcing merit based governance within public administration. The judgment contributes to the development of Indonesian administrative law by strengthening legal protection, promoting responsible administrative decision making, and enhancing institutional commitment to professional and rule based civil service governance.